PSYCHOLOGICAL ASPECTS OF THE MANIFESTATION OF LEADERSHIP QUALITIES - Mirabdullaeva Shoirakhon Abdulkhaevna (Ecominds Press, 2025)
The article describes the concept of leadership, its specific psychological aspects, leadership qualities, and also provides information on the qualities characteristic of leaders.
Keywords: Leader, leader, goal, problem, task, management, boss, organization, manager, group.